Numerical dynamic simulation of optimized cross-flow heat exchanger with various refrigerants - Kahar, Osman; Rudiyanto, P. Jong; M. Shahril, Salleh (American Institute of Physics, 2011)
Link to publisher's homepage at http://www.aip.org/